You know the fair rule and much more : strategies for making the hard job of discipline and behaviour management in school easier - Rogers, William A. 1947- (ACER, 1998)
Discipline: definition and protocols. Disruptive behaviour and teacher management style. Classroom management. Rights and rules in the classroom. Supports to behaviour management. Building a positive classroom climate. The hard-to-manage class. Conflict resolution and managing anger.